The Impact of Economic Pressure on Parent Positivity, Parenting, and Adolescent Positivity into Emerging Adulthood. Issue 1 (February 2015) - Neppl, Tricia K.; Jeon, Shinyoung; Schofield, Thomas J.; Donnellan, M.Brent
<x xml:space="preserve">Abstract</x> This study describes how positivity can be incorporated into the family stress model to explain resilience to disrupted family processes in the face of economic distress. Prospective, longitudinal data came from 451 mothers, fathers, and youth participating from their adolescence through early adulthood. Assessments included observational and self‐report measures. Information regarding economic pressure, parental positivity, and parenting were collected during early adolescence, positivity was collected in late adolescence and emerging adulthood. Results indicated that economic pressure was indirectly associated with adolescent positivity through parental positivity. Economic pressure was negatively associated with parent positivity, whereas parental positivity was positively associated with parenting. Moreover, parental positivity and parenting were related to positivity in adolescence. Results suggest that personal resources linked to a positive outlook can foster nurturant parenting, even in times of economic strain. Such parenting seems to positively influence adolescent development into emerging adulthood.